2007
DOI: 10.1159/000100386
|View full text |Cite
|
Sign up to set email alerts
|

The Application of an Enamel Matrix Protein Derivative (Emdogain®) in Regenerative Periodontal Therapy: A Review

Abstract: Regenerative periodontal therapy aims at reconstitution of the lost periodontal structures such as new formation of root cementum, periodontal ligament and alveolar bone. Findings from basic research indicate that enamel matrix protein derivative (EMD) has a key role in periodontal wound healing. Histological results from animal and human studies have shown that treatment with EMD promotes periodontal regeneration. Moreover, clinical studies have indicated that treatment with EMD positively influences periodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 245 publications
(164 reference statements)
0
52
0
3
Order By: Relevance
“…Attachments are characterized by the presence of new acellular and/or cellular cementum with inserting collagen fibers and new alveolar bone [22]. Although Emdogain Ò has been commercialized for just over a decade, it is widely used in periodontical practice and for replanting teeth [20,21]. Results from basic research have suggested that EMD has an important role in periodontal wound healing.…”
Section: Biological Approaches To Periodontal Regenerationmentioning
confidence: 99%
“…Attachments are characterized by the presence of new acellular and/or cellular cementum with inserting collagen fibers and new alveolar bone [22]. Although Emdogain Ò has been commercialized for just over a decade, it is widely used in periodontical practice and for replanting teeth [20,21]. Results from basic research have suggested that EMD has an important role in periodontal wound healing.…”
Section: Biological Approaches To Periodontal Regenerationmentioning
confidence: 99%
“…It is extracted from developing embryonal enamel of porcine origin and contains several matrix proteins from the amelogenin family. Several studies have shown that EMD influences the migration, attachment, proliferative capacity and biosynthetic activity of periodontal ligament cells [59,[67][68][69].…”
Section: Platelet Rich Plasma (Prp)mentioning
confidence: 99%
“…A commercially prepared and purified extract of enamel matrix proteins, EMD is composed primarily of amelogenin and has been shown to promote PDL fibroblast proliferation and growth [10]. The effects of Emdogain are thought to be the induction of proliferation, migration, adhesion, mineralization and differentiation of cells in periodontal tissue.…”
Section: Emdogain or Enamel Matrix Derivative (Emd) Developed Bymentioning
confidence: 99%